Reinterpreting the Carok Tradition: : Discourse on Identity and Power in Madurese Culture - A Zahid; Rohma Ivantri; Muhammad Ghufron; Indana Zulfa (Faculty of Social Science, Universitas Negeri Malang, 2026)
The tradition of carok is often viewed as a form of violence inherent in Madurese society. However, this study shows that carok is not merely a brutal act, but rather a social discourse that represents the values of honor, identity, and power in Madurese cultural structures. This study aims to reinterpret the meaning of carok through a socio-anthropological approach using Michel Foucault's discourse theory. The method used is qualitative with an ethnographic approach, involving in-depth interviews, participatory observation, and group discussions in four districts in Madura: Bangkalan, Sampang, Pamekasan, and Sumenep. The results of the study show a shift in the meaning of carok from a symbol of violence to a representation of moral struggle and social identity. The discourse of carok is produced and reproduced through power relations between the community, religious leaders, and the media, which shape a new understanding of honor and conflict resolution. This study emphasizes the importance of reinterpreting local culture as an effort to deconstruct stereotypes of violence in Madurese society, while offering a model of conflict resolution based on human values and local wisdom.